2019
DOI: 10.3390/polym11111869
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Stabilized Liquid Crystal Smart Window with Flexible Substrates Based on Low-Temperature Treatment of Polyamide Acid Technology

Abstract: Polymer stabilized liquid crystal (PSLC) devices can be used as smart privacy windows that switch between transparent and opaque states. The polyimide alignment layer of a PSLC device is usually obtained by the treatment of polyamide acid (PAA) with temperatures over 200 °C. This hinders the fabrication of PSLC devices on flexible substrates, which melt at these high temperatures. In this work, the fabrication of a PSLC alignment layer using a lower temperature that is compatible with most flexible substrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…The LC mixture is often used for the fabrication of LC‐based smart windows, due to its relatively large birefringence and dielectric anisotropy. [ 8,9 ] The LC mixture belongs to the (−, +) type, where the first − sign means negative dielectric anisotropy and the second + sign means positive conductivity anisotropy (∆σ = σ // – σ ⊥ ). After mixing with 0.1 wt% zwitterion Reichardt's dye, the mixture shows a clearing temperature around 93 °C (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LC mixture is often used for the fabrication of LC‐based smart windows, due to its relatively large birefringence and dielectric anisotropy. [ 8,9 ] The LC mixture belongs to the (−, +) type, where the first − sign means negative dielectric anisotropy and the second + sign means positive conductivity anisotropy (∆σ = σ // – σ ⊥ ). After mixing with 0.1 wt% zwitterion Reichardt's dye, the mixture shows a clearing temperature around 93 °C (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Liquid crystal (LC) is an interesting class of materials with anisotropic optical and dielectric properties, which is widely used in liquid crystal displays (LCDs), smart windows, adaptive coatings, and many other electro‐optic devices. [ 1–9 ] One field‐induced effect in LCs is called electroconvection (EC), or electro‐hydrodynamic instability (EHDI), which is a dissipative process associated with the occurrence of a mechanical flow and relatively large electric current. [ 10 ] It is well known as one of the first LCD technologies, and has been extensively studied as a model system for the formation of regular nonequilibrium structures, such as rolls, chevrons, squares, fingerprint, bimodal varicose, and cellular or wavy patterns.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the fabrication of PSLC on the flexible films, as they usually melt or degrade at such high temperatures. Zhang et al reported that low-temperature (incomplete imidization) treatment of PAA neither negatively affects the homeotropic alignment of the LCs, nor impacts the formation of a polymer network on PSLC [34] (Figure 4a). The results presented herein lay a solid foundation for the development of flexible PSLC films.…”
Section: Polymer Stabilized Liquid Crystals (Pslcs)mentioning
confidence: 99%
“…The preliminary results indicate improved adhesion strength at the interface [35]. We believe that once successfully developed, flexible PSLC films shall accelerate the advancement of the field related to smart windows.. [34]. Cross-sectional SEM images of the polymer networks (for PSLC) with alignment layers fabricated using b) polyimide and c) bifunctional silanes [35].…”
Section: Polymer Stabilized Liquid Crystals (Pslcs)mentioning
confidence: 99%
See 1 more Smart Citation